Stability of Anisotropic Pressure Tokamak Equilibria to Ideal Ballooning Modes - Bishop, Christopher; Hastie, R.J. (Nuclear Fusion, 1985)
The effect of pressure anisotropy on the stability of ideal-MHD ballooning modes is studied for a large-aspect-ratio tokamak of circular cross-section. Significant increase of the perpendicular energy of electrons or ions can cause strong modifications of the stability boundary, especially at low shear.